In Vivo Bioluminescence Imaging Validation of a Human Biopsy–Derived Orthotopic Mouse Model of Glioblastoma Multiforme - Monika A. Jarzabek; Peter C. Huszthy; Kai O. Skaftnesmo; Emmet McCormack; Patrick Dicker; Jochen H.M. Prehn; Rolf Bjerkvig; Annette T. Byrne (Molecular Imaging)
Glioblastoma multiforme (GBM), the most aggressive brain malignancy, is characterized by extensive cellular proliferation, angiogenesis, and single-cell infiltration into the brain. We have previously shown that a xenograft model based on serial xenotransplantation of human biopsy spheroids in immunodeficient rodents maintains the genotype and phenotype of the original patient tumor. The present work further extends this model for optical assessment of tumor engraftment and growth using bioluminescence imaging (BLI). A method for successful lentiviral transduction of the firefly luciferase gene into multicellular spheroids was developed and implemented to generate optically active patient tumor cells. Luciferase-expressing spheroids were injected into the brains of immunodeficient mice. BLI photon counts and tumor volumes from magnetic resonance imaging (MRI) were correlated. Luciferase-expressing tumors recapitulated the histopathologic hallmarks of human GBMs and showed proliferation rates and microvessel density counts similar to those of wild-type xenografts. Moreover, we detected widespread invasion of luciferase-positive tumor cells in the mouse brains. Herein we describe a novel optically active model of GBM that closely mimics human pathology with respect to invasion, angiogenesis, and proliferation indices. The model may thus be routinely used for the assessment of novel anti-GBM therapeutic approaches implementing well-established and cost-effective optical imaging strategies.